Causalismo e interpretacionismo en la explicación psicológica: el caso del psicoanálisis - Braun Gutiérrez, Ricardo (1998)
From a philosophical standpoint, the psychoanalytic model as a form of scientific explanation is discussed. As an extension of folk psychology, psychoanalyss posits the existence of beliefs and desires, and explains human behavior as a result of the causal interaction of unconscious beliefs and desires. If, as it is argued, psychoanalysis is a medical science, it ought to be committed to a realistiv view of the etiology of neuroses. However, due to the lack of a theory of truth, the recollection of data and their further interpretation are beset with arbitrariness. Thus, interpretations have an instrumental value for therapeutic outcome. In sum, psychoanalysis is no committed to a realistic view of folk psychology.